Characterization of the abrasion resistance and the acoustic wave attenuation of the engineered cementitious composites for runway pavement. (20th June 2018) - Wu, Chao; Pan, Yang; Ueda, Tamon
Highlights: The abrasion resistance and the acoustic wave attenuation of ECC were characterized through experimental tests. The compressive and tensile strengths of ECC can be affected by the fiber volume ratio. The abrasion resistance of ECC is mainly dependent on the compressive and tensile strengths. The acoustic wave attenuation of ECC is linearly related to its void ratio. Abstract: Concrete runway pavement is subjected to a critical issue of brittle cracking, which is hazardous for the safety operation of the airport. Engineered cementitious composite (ECC) is a promising pavement material due to its ductility with a strain capacity up to 5%, as well as its desirable micro-cracking and self-healing properties. However, the abrasion resistance and acoustic wave attenuation of ECC, which are important behaviors for a pavement, have not been quantified yet. This paper presents an experimental program to investigate the abrasion resistance and the acoustic wave attenuation of ECC. The experimental results showed that the abrasion resistance of ECC (with 3% fiber volume ratio) could be comparable with the ordinary concrete of the same compressive strength. It was also found that, the acoustic wave attenuation of ECC was positively related with its fiber volume ratio and much higher than that of the ordinary concrete with the same compressive strength. It was interesting to find that the acoustic wave attenuation of ECC was independent of the wave frequency (ranging from 200 Hz to 2000 Hz) of the acoustic signal. The underlying mechanisms for the abrasion resistance and acoustic wave attenuation of ECC were discussed with the measurement of its void ratio, compressive and tensile properties.